Proton pump inhibitors do not increase the risk for recurrent spontaneous bacterial peritonitis in patients with cirrhosis. Issue 5 (27th April 2017) - Kim, Jung Hee; Lim, Kyung Sook; Min, Yang Won; Lee, Hyuk; Min, Byung‐Hoon; Rhee, Poong‐Lyul; Kim, Jae J; Koh, Kwang Cheol; Paik, Seung Woon
Abstract: Background and Aim: The present study aimed to assess the real impact of proton pump inhibitor (PPI) use on incidence of recurrent spontaneous bacterial peritonitis (SBP) in a homogenous population composed of cirrhotic patients with a previous SBP where differences related with SBP incidence between PPI users and non‐users are less likely to exist. Methods: This retrospective cohort study enrolled 307 cirrhotic patients taking diuretics for ascites control and had a previous SBP. Patients who took any PPI for at least 1 week prior to a second SBP were included in the PPI group. The incidence of a second SBP was a primary outcome and was compared between PPI group and non‐PPI group before and after propensity score matching. Risk factors for a second SBP were investigated by multivariate analysis. Results: Second SBP occurred in 17 patients (29.3%) during mean 52.1 ± 5.2 months of PPI group and in 60 patients (24.1%) during mean 61.9 ± 4.8 months of non‐PPI group, which did not differ ( P  = .185). In the matched cohort, second SBP similarly occurred in both groups [29.3% of PPI group vs 26.8% of non‐PPI group ( P  = .271)]. According to the multivariate analysis, Child–Pugh score was the only significant risk factor for a second SBP (hazard ratio 1.68, 95% confidence interval, 1.13–2.50, P  = .001). Isolated bacteria and clinical outcomes such as of mortality, presence of sepsis, and hospital stay did not differ between the two groups in the matched cohort. Conclusion: Proton pump inhibitor use is not a risk factor for recurrent SBP in cirrhotic patients.